2016
DOI: 10.1055/s-0041-108295
|View full text |Cite
|
Sign up to set email alerts
|

Resistenzmechanismen unter antihormoneller Therapie des fortgeschrittenen Prostatakarzinoms

Abstract: With the development of Abiraterone and Enzalutamide new treatment option have become available in addition to Docetaxel for first-line treatment of castration resistant prostate cancer. However, resistance and ultimately failure occurs inevitably with all available treatment options. Moreover, cross-resistance leads to considerably reduced efficacy in second-line treatment. Preclinical data suggest discriminative mechanisms of resistance development for Abiraterone and Enzalutamide. Clinical confirmation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
1
2
0
3
Order By: Relevance
“…Resistance to anti-cancer therapies is facilitated through an array of mechanisms that vary across tumor types [63, 64]. In the present study, we demonstrated that RES modulates mitochondria-mediated, caspase-independent apoptosis in murine prostate cancer cells.…”
Section: Discussionsupporting
confidence: 59%
“…Resistance to anti-cancer therapies is facilitated through an array of mechanisms that vary across tumor types [63, 64]. In the present study, we demonstrated that RES modulates mitochondria-mediated, caspase-independent apoptosis in murine prostate cancer cells.…”
Section: Discussionsupporting
confidence: 59%
“…RM-581 was significantly more active than all the drugs tested at 1 and 5 µM except for docetaxel tested at 1 µM, which showed slight but significantly higher potency. As a second step, we performed an assay using multiple concentrations from 1 nM to 10 µM to better compare the anticancer potency between RM-581 and docetaxel ( Figure 5 B), a cytotoxic agent established in the last few decades as a gold standard for metastatic CRPC cases [ 8 , 10 , 11 , 17 , 18 ]. In this assay and others, the antiproliferative activity of docetaxel showed an unexpected profile depending on concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Abiraterone acetate (an inhibitor of androgen biosynthesis) [ 12 ], enzalutamide (a new generation of antiandrogen) [ 13 ], and cabazitaxel (a new generation of taxotere) [ 14 ] are three relevant examples of new drugs obtained from these research efforts that significantly impacted the median survival of CRPC patients [ 15 , 16 ]. However, resistance again occurs, even for those new drugs, leaving these resistant patients with no viable therapeutic options [ 17 , 18 ]. The development of innovative molecules acting by different mechanisms of action are thus urgently needed to give new hope to these doomed PCa patients [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ein Grund könnte sein, dass unter Apalutamid plus ADT in der TITAN-Biomarkerpopulation signifikant weniger Androgenrezeptor-Aberrationen als unter alleiniger ADT festgestellt wurden [18]. Denn antihormonelle Therapien können durch Androgenrezeptor-Veränderungen zu Resistenzen führen, die deren Wirksamkeit sowie auch die Wirksamkeit von anderen antihormonellen Therapien als Folgetherapie beeinflussen können [19]. Die Wirksamkeit lässt sich aber weder quantifizieren noch zwischen den einzelnen Folgetherapien differenzieren.…”
Section: Behandlungsoptionen Im Progressunclassified